MoS0.5Se1.5 embedded in 2D porous carbon sheets boost lithium storage performance as an anode material - Li, Tongfei (2019)
A promising anode material is developed for Li‐ion batteries consisting of MoS0.5Se1.5 particles uniformly embedded in 2D porous carbon sheets (denoted as MoS0.5Se1.5/C sheets). The formation of MoS0.5Se1.5/C sheets depends on a facile and cost‐effective potassium chloride (KCl)‐assisted strategy. The micrometer‐level KCl crystals are selected as the solid template because they are more easily precipitated than metal precursors and carbon source during recrystallization, which drives the simultaneous formation of carbon sheets and MoS0.5Se1.5 particles on KCl surface after pyrolysis; while makes a tighter integration between MoS0.5Se1.5 and carbon sheets. As an anode for Li‐ion batteries, the MoS0.5Se1.5/C sheets show more excellent Li storage properties compared to that of S‐free MoSe2/C sheets, including excellent cyclic stability and high rate capacity. Specifically, 494.8 mA h g−1 at a current density of 100 mA g−1 still is maintained for MoS0.5Se1.5/C sheets after 200 cycles, which is much higher than that of MoSe2/C sheets (173.5 mA h g−1). The significantly enhanced performance of MoS0.5Se1.5/C sheets can be attributed to the synergistic combination of MoS0.5Se1.5 phase and porous carbon sheets, which provides an effective conductive matrix and buffer spaces for Li‐ion/electronic transfer and MoS0.5Se1.5 expansion, during the charge–discharge.